Christological Reflection of John Hick (1922-2012) as Relativize the Uniqueness of Jesus Christ's Salutary Mediation - Ignacy Bokwa (The Francis de Sales Scientific Society (TNFS.PL), 2022)
Pluralistic theology of religion is a real threat to Christianity. It relativizes the unicity of saving mediation of Jesus Christ in the name of democratic equalityof all religions. The Congregation for the Doctrine of the Faith recognized this threat and published "Dominus Iesus" declaration in 2000. This document refers, inter alia,  to the creativity of John Hick (1922-2012).  The English philosopher of religion is one of the best known and the most prominent representatives of the pluralistic theology of religion. This theory treats all religions as equal ways of salvation. The absolute claim of Christianity is severely criticized.  John Hick's contribution to this criticism is about relativization of Jesus Christ's salutary meaning. Hick questions the dogmatic and ontological language of the first christological council in Nice (325) and Chalcedon (451). He accuses this language of abandoning the imagery of the biblical language. According to Hick Jesus Christ is not a genuine Son of God- He is one of God's embodiments. The article analyzes John Hick's pieces of writing and ends with a critical conclusion.